2022
DOI: 10.1155/2022/6256384
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of lncRNA XIST Ameliorates IL-1β-Induced Apoptosis of HUVECs and Change of Tissue Factor Level via miR-103a-3p/HMGB1 Axis in Deep Venous Thrombosis by Regulating the ROS/NF-κB Signaling Pathway

Abstract: Background. The effect of lncRNA X inactive-specific transcript (XIST) inducing cardiovascular diseases on deep vein thrombosis (DVT) and its mechanism has not been reported. In this study, we uncovered the mystery that lncRNA XIST causes DVT with HUVEC dysfunction. Method. The expression levels of lncRNA XIST and miR-103a-3p were detected by qRT-PCR, and HMGB1 expression was determined by qRT-PCR and western blot. The correlations among the expression levels of lncRNA XIST, miR-103a-3p, and HMGB1 were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“… 21 Hypertension and diabetes can lead to vascular endothelial cell damage and thrombosis formation due to metabolic disorders. 3 Additionally, NEAT1 has been shown to participate in the alleviation of diabetic retinopathy through crocetin treatment. 22 High glucose induces a time-dependently upregulates of NEAT1 expression, which is elevated in diabetic nephropathy and accelerates proliferation, oxidative stress, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 21 Hypertension and diabetes can lead to vascular endothelial cell damage and thrombosis formation due to metabolic disorders. 3 Additionally, NEAT1 has been shown to participate in the alleviation of diabetic retinopathy through crocetin treatment. 22 High glucose induces a time-dependently upregulates of NEAT1 expression, which is elevated in diabetic nephropathy and accelerates proliferation, oxidative stress, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, when endothelial cell damage or apoptosis impairscells damage or apoptosis impairs their normal anticoagulant effect, promoting thrombosis, and affecting intravascular reactive substance levels to aggravate thrombosis. 3 , 29 The importance of vascular endothelial cells necessitates investigation into mechanisms in vitro. Mechanistically, we found that NEAT1 significantly inhibited HUVECs proliferation and migration while increasing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, XIST is also associated with preeclampsia and cancer [100,101]. This lncRNA was found to be highly expressed in the plasma of DVT patients, possibly acting as a decoy by sponging miR-103a-3p, which in turn, targets highmobility group box 1 (HMGB1) [102]. Concordantly, miR-103a-3p expression was found to be reduced in patients with unprovoked VTE [103].…”
Section: Xistmentioning
confidence: 92%